PENERAPAN MODEL PEMANDU AWAL (ADVANCE ORGANIZER) DALAM MENINGKATKAN PEMAHAMAN KONSEP IPA SISWA SEKOLAH DASAR - Nur Sapitri (ADISAM PUBLISHER, 2026)
Science learning in elementary schools requires students to understand concepts deeply, not merely memorize facts. However, in practice, many students experience difficulties in understanding concepts because teaching methods are still conventional. This study aims to determine the implementation of the Advance Organizer learning model in improving elementary school students’ understanding of science concepts. The research method used is a literature study by analyzing various research findings related to the use of the Advance Organizer model in science learning in elementary schools. The results of the review indicate that the Advance Organizer model is able to help students connect prior knowledge with new concepts so that learning becomes more meaningful. In addition, the implementation of this model has also been proven to improve learning outcomes, conceptual understanding, and students’ thinking abilities. Therefore, the Advance Organizer learning model can be used as an alternative and effective learning strategy to improve students’ understanding of science concepts in elementary schools.